An assessment of indoor air quality in two contrasting buildings in London - Mohd Aris, Mohd Shukri; Barratt, Benjamin; Kelly, Frank (2011)
Background: People spend most of their time indoors in buildings such as schools and offices as well as their homes. Over recent years there has been increased interest in Indoor Air Quality (IAQ) suggesting that the contribution of outdoor pollutant penetration and indoor airborne particulate and gaseous pollutants may be responsible for the aggregation of a number of respiratory illnesses. Because of these possible health implications it is important to understand the characteristics of each air pollutant inside/outside (I/O) the building and the variables affecting the degree of exposure. The findings from this study will be used to establish a London Indoor Air Quality Network to compliment the existing outdoor network.